MADRASAH HEAD SUPERVISION MANAGEMENT IN IMPROVING TEACHER PROFESSIONALISM IN PRIVATE IBTIDAIYAH MADRASAH (MIS) INTEGRATED ISLAM (IT) RAUDHOTUL QURRO TANJUNGBALAI CITY - Aswin, Aswin; Arsyad, Junaidi; Nahar, Syamsu (UIN Sumatera Utara Medan, 2023)
This research aims to describe the supervision management of madrasah principals in increasing teacher professionalism at MIS IT Raudhotul Qurro. This study used qualitative research methods. Data collection in this research was carried out using observation techniques, interviews and documentation studies. The aim of this research is to determine the supervision techniques of madrasa heads, models of supervision of madrasa heads, and evaluation of supervision of madrasa heads at MIS IT Raudhotul Qurro. The findings of this research are that supervision techniques for madrasah heads are carried out using individual techniques and group techniques. Individual techniques are carried out by visiting classes, making observations, guiding teachers to overcome problems faced by students.